2022
DOI: 10.3390/ijerph191811324
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Use and Application of Systematic Tailored Assessment for Responding to Suicidality (STARS) Protocol Following Original Training

Abstract: Background: Understanding the use of Systematic Tailored Assessment for Responding to Suicidality protocol (STARS-p) in practice by trained mental health practitioners over the longer- term is critical to informing further developments. The study aim was to examine practitioners’ experiences of STARS-p and factors associated with its use in practice over a 12–24-month period after training. Method: Practitioners who undertook the STARS-p training completed an online survey 12–24 months post training. The surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Three participants reported using published risk assessment tools (e.g. the Suicide Tailored Assessment for Responding to Suicidality; Hawgood & de Leo, 2018). Another three participants indicated that they adapt these tools, such as modifying the questions to ensure that they are developmentally appropriate, or appropriate for neurodivergent clients with limited verbal skills.…”
Section: Resultsmentioning
confidence: 99%
“…Three participants reported using published risk assessment tools (e.g. the Suicide Tailored Assessment for Responding to Suicidality; Hawgood & de Leo, 2018). Another three participants indicated that they adapt these tools, such as modifying the questions to ensure that they are developmentally appropriate, or appropriate for neurodivergent clients with limited verbal skills.…”
Section: Resultsmentioning
confidence: 99%
“…Training exists for MHPs in intermediate risk assessment and crisis response planning. These include, but are not limited to, Systematic Tailored Assessment for Responding to Suicidality protocol (STARS-protocol; Hawgood & De Leo, 2018; Hawgood, Ownsworth, Kõlves, et al, 2022; Hawgood, Woodward, et al, 2022), Commitment to Living (CTL)/SafeSide training (Pisani et al, 2012, 2016), Crisis Response Planning (CRP; Bryan et al, 2017), Counseling for Access to Lethal Means (e.g., Sale et al, 2018), and the Suicide Safety Plan Intervention (SPI; B. Stanley et al, 2018).…”
Section: A Tiered Approach To Suicide Prevention Trainingmentioning
confidence: 99%
“…The STARS-protocol (Hawgood & De Leo, 2018) represents an emerging alternative approach to prediction-based assessment processes. STARS-protocol is a semistructured, collaborative interview process involving engagement between client and MHP to explore psychosocial needs of the client and their suicidality within their life context to inform safety planning and support responses (Hawgood, Ownsworth, Mason, et al, 2022).…”
Section: The Ccm Of Suicide Prevention Training: Foundation and Appli...mentioning
confidence: 99%
See 2 more Smart Citations